Rancang Bangun Alat Praktikum Resonansi Bunyi Dengan Menentukan Cepat Rambat Bunyi Di Udara Pada Pipa Kecil dan Pipa Besar - Nina Amelia; Nilam Cahya Kusumaningtyas; Adinda Rahma H F; Ayu Sulistiyowati; Jazilatul Mufida; Subiki . (Peneliti.net, 2023)
The design of a sound resonance practicum tool is designed to determine the differences in the speed of sound propagation in air in small pipes and large pipes. The tool is designed based on the concept of sound resonance which is carried out on large and small pipes immersed in water to find harmonic frequencies with the help of a frequency generator application of 1250, 1500 and 1750 Hz. The practical design of the tool and the simple experimental procedure make it easy to use. Experimental results on small pipes with a frequency of 1250, 1500 and 1750 Hz obtained the length of the air column (L) of 13.603, 11.33 and 9.73 m with the speed of sound in air (v) of 340, 340 and 340, 5m/s. In large pipes with a frequency of 1250, 1500 and 1750 Hz, the length of the air column (L) is 13.6, 11.34 and 9.73 m with the speed of sound in air (v) of 340, 340 and 340, 5m/s. Based on the experimental results, there is no difference in results and the relationship between the magnitude of the frequency and the length of the air column is the same, that is, it is inversely proportional, while the value of the speed of sound in air tends to be constant at a value of 340 m/s – 340.5 m/s.